Hubungan Pendidikan Kesehatan terhadap Perilaku Ibu dalam Pencegahan Kejang Demam pada Anak Usia 0-5 Tahun - Nurhanisah, Hana; Kamilah, Siti (Journal of Nursing Education and Practice, 2023)
Introduction: Seizure fever wrong a disturbance neurologic that very often in see you on time children, especially on aged 0-5 years. Seizure fever is an attack seizure that occurs because of an increased temperature body (temperature rectal on 380C). Objectives: Study this aim to know the connection between the education and health behavior of mothers in the prevention of seizure fever in children aged 0-5 years. Method: This research uses quantitative research with correlation research and uses a cross-sectional design where the population in this study is children aged 0-5 in Karyabakti Cidaun village with a sample size of 60 people. The sampling technique used is random sampling. The instrument consists of 2 questionnaires, namely a maternal behavior questionnaire and a questionnaire for the prevention of febrile seizures in children 0-5 years which was created by the researcher himself. The data analysis used in this research was univariate and bivariate analysis using the chi-square test.   Result: Results study found that based on the analysis connection between the education and health behavior of mothers in the prevention of seizure fever in children aged 0-5 years in earn that there are as many as 15 (39,5 %) respondents with education health good and behavior mother positive. Whereas respondents with education health not good and behavior mother negative there is as much 23 (60,5 %). The relationship between health education and maternal behavior in preventing febrile seizures in children aged 0-5 years was obtained with a p-value = 0.000, less than 0.05. Conclusion: There is a relationship between health education and maternal behavior in preventing febrile seizures in children aged 0-5 years in Karyabakti Cidaun village.